Peran Filsafat Hukum dalam Pembentukan Hukum di Indonesia - Bakir, Bakir (JURNAL AT-TURAS, 2017)
Law is, first and foremoest, a discursive discipline: lawyers and judges live in the doain of reasons and meaning. It interprets statutes and cases, articulate rules to guide behavior, and then argue about their import in particular cases. Meanwhile, philosophy is, of course, the discursive discipline par excellence to which English philosopher John Campbell quite perceptively described as ‘thinking in slow motion’, a meaning which seems contraproducive with lawyering as often called as ‘thinking in fast motion’. This article argues that philosophy of law has important role on implementation of law in Indonesia. Given the fact that both (law and philosophy) are, as discursive disciplines, concerned with rational and logical thought, the philosophy inquiry into law simply brings to light and makes explicit what is often implicit and unargued.